Anti-Tumoral and Anti-Angiogenic Effects of Low-Diluted Phenacetinum on Melanoma - Fuselier, Camille; Quemener, Sandrine; Dufay, Eleonore; Bour, Camille; Boulagnon-Rombi, Camille; Bouland, Nicole; Djermoune, El-Hadi; Devy, Jérôme; Martiny, Laurent; Schneider, Christophe (Frontiers in Oncology, 2021)
Melanoma is the most aggressive form of skin cancer and the most rapidly expanding cancer in terms of worldwide incidence. If primary cutaneous melanoma is mostly treated with a curative wide local excision, malignant melanoma has a poor prognostic and needs other therapeutic approaches. Angiogenesis is a normal physiological process essential in growth and development, but it plays also a crucial role in the crossing from benign to advanced state in cancer. In melanoma progression, angiogenesis is widely involved during the vertical growth phase. Currently, no anti-angiogenic agents are efficient on their own and combination of treatments will probably be the key to success. In the past, phenacetin was used as an analgesic to releave pain, causing side effects at large dose and tumor-inducing in humans and animals. By contrast, Phenacetinum low-dilution is often used in skin febrile exanthema, patches profusely scattered on limbs, headache or flushed face without side effects. Herein are described the in vitro, in vivo and ex vivo anti-angiogenic and anti-tumoral potentials of Phenacetinum low-dilution in a B16F1 tumor model and endothelial cells. We demonstrate that low-diluted Phenacetinum inhibits in vivo tumor growth and tumor vascularization and thus increases the survival time of B16F1 melanoma induced-C57BL/6 mice. Moreover, Phenacetinum modulates the lung metastasis in a B16F10 induced model. Ex vivo and in vitro, we evidence that low-diluted Phenacetinum inhibits the migration and the recruitment of endothelial cells and lead to an imbalance in the pro-tumoral macrophages and to a structural malformation of the vascular network. All together these results demonstrate highly hopeful anti-tumoral, anti-metastatic and anti-angiogenic effects of Phenacetinum low-dilution on melanoma. Continued studies are needed to preclinically validate Phenacetinum low-dilution as a complementary or therapeutic strategy for melanoma treatment.